MLKL Regulates Rapid Cell Death-independent HMGB1 Release in RSV Infected Airway Epithelial Cells - Simpson, Jennifer; Spann, Kirsten M.; Phipps, Simon (Frontiers in Cell and Developmental Biology, 2022)
Respiratory syncytial virus (RSV)-induced bronchiolitis is a significant contributor to infant morbidity and mortality. Previously, we identified that necroptosis, a pro-inflammatory form of cell death mediated by receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and RIPK3, and mixed lineage kinase domain like protein (MLKL), occurs in RSV-infected human airway epithelial cells (hAECs), mediating the release of the alarmin high mobility group box 1 (HMGB1). Here, we show that RSV infection of hAECs induces the biphasic release of HMGB1 at 6 (‘early’) and 24 (‘late’) hours post infection (hpi). The early phase of HMGB1 release at 6 hpi is cell death-independent, however, this release is nonetheless attenuated by inhibition of MLKL (primarily associated with necroptosis). The early release of HMGB1 promotes the late phase of HMGB1 release via the activation of RAGE (receptor for advanced glycation endproducts) and occurs with cell death. Treatment of hAECS with exogenous HMGB1 combined with a pan-caspase inhibitor induces hAEC necroptosis, and is attenuated by the RAGE antagonist, FPS-ZM1. Together, these findings demonstrate that RSV infection of hAECs leads to the early release of HMGB1, followed by a paracrine feed-forward amplification loop that further increases HMGB1 levels and promotes cell death. As the inhibition of MLKL or targeting of HMGB1/RAGE pathway attenuates the release of pro-inflammatory HMGB1 and decreases viral load, this suggests that the pharmacological targeting of these pathways may be of benefit for the treatment of severe RSV bronchiolitis.